A novel dynamic holding system for thin metal plate shearing machines. (April 2017) - Araújo, L.M.B.; Silva, F.J.G.; Campilho, R.D.S.G.; Matos, J.A.
Abstract: Metal shearing machines are heavy equipments usually linked to low added-value due to the small amount of technological devices incorporated. However, this situation can be changed through equipment designers' creativity. Analysing some specific operations, it can be observed that some tools, when coupled to the equipment, should substantially increase the cutting process productivity and the final product quality. Regarding the thin metal plates shear process, it can be found that in the cutting final stage, the cut material weight is suspended by a small material section still requiring to be cut. This leads to strip tip deformation, causing poor quality of the final product, which cannot stay fully plan. This work was developed around this problem, studying the best solution to develop a new tool able to avoid the lack of plate flatness after cut. A novel equipment was designed, able to be easily connected to the shearing machine, following the blade movement throughout cut operation. The system is fully-automated, being operated by a single cut instruction given by the machine operator. This system allows the manufacturing company to increase the added-value of each machine, offering advanced and desirable solutions to the customers, and contributing as well to the company business sustainability. Highlights: The guillotine cut of lengthy and thin sheet metal plates presents deformation problems. The device now presented avoids the deformation of the sheet metal at the end of the cutting line. This device is based in four pneumatic cylinders properly programmed and controlled. More than one solutions are provided, allowing the costing management. This device can be applied in new machines or machines already in service.